The heart of a rebel poet : letters of Michael Madhusudan Dutt - Dutt, Michael Madhusudan. 1824-1873.; Ghulam Murshid (New Delhi : Oxford University Press, 2004)
Letters of a 19th century Bengali poet who wrote in both Bengali and English.
Includes bibliographical references p. 311-319 and index.
Keywords: Dutt, Michael Madhusudan, -- 1824-1873 -- Correspondence; Poets, Bengali -- 19th century -- Correspondence; Authors, Bengali -- 19th century -- Correspondence